Performance of Valuation Methods in Financial Transactions - Heller, David (Wiley-ISTE, 2021)
MODERN FINANCE, MANAGEMENT INNOVATION & ECONOMIC GROWTH SET Coordinated by Faten Ben Bouheni Financial operations depend on potential value creation, the nature of the shareholder base, the level of development of the company and its growth prospects. They result from different commercial and financial strategies that must integrate the interest of the capital holders, the influence and strategy of the group in the initiative and the structure of the offer. This book examines how, in practice, a company's capital is structured, taking into account the interests of various stakeholders. The performance of valuation methods, which serve investors in their decision-making and financial arrangements, is developed in detail. Depending on the contexts present in the control market, the methods of stock market and transactional comparables, discounted cash flows and the patrimonial approach, will be favored to assess the value of a company's shares. Performance of Valuation Methods in Financial Transactions is an in-depth analysis of equity transactions and is aimed at students and corporate finance professionals.